Analisis Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum - Faisal Harahap, Raja Ahmad; Fahmi, Khairul (JPPUMA Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2019)
This study aims to analyze Law Number 7 of 2017 concerning General Elections, relating to the management of the duties, obligations and authority of polling group administrators in 2019 elections. Besides analyzing the health aspects of polling group officers in 2019 elections due to post-implementation 2019 elections many officers of the Organizers of the Voting Group died and were sick in a number of Indonesian regions. This research method uses a qualitative approach by conducting literature studies from various relevant sources. The results of this study indicate that the need to manage the duties, obligations and authority of the Voters Organizing Group officers proportionally both at the stage of voting and also the vote count. In addition, it is necessary to pay attention to the health aspects of the polling group officers. That should be allegedly caused by a complicated simultaneous electoral system and unpreparedness in the management of election management.